PENGGUNAAN PETA KONSEP DALAM MENINGKATKAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI BAGI MAHASISWA PGSD STKIP MUHAMMADIYAH MUARA BUNGO - aprizan - (LPPM Universitas Muhammadiyah Muara Bungo, 2019)
The background of this study is the low writing skill of students at PGSD STKIP Muhammadiyah Muara Bungo in Indonesia. This study aims to describe the implementation of learning writing of description text by using mind map at PGSD STKIP Muhammadiyah Muara Bungo. This research is a Classroom Action Research (CAR) with four stages of activities namely planning, action, recognition and reflection. The results of the data analysis can be concluded that the use of mind map can improve the writing skills of students PGSD STKIP Muhammadiyah Muara Bungo.